The Relationship Between Service Quality and Passengers Satisfaction: A Case of Air Asia Passengers - Athirah, Mohd Tan (2011)
This study is to determine the level of passenger’s satisfaction among Air Asia Passengers and to determine the influence of service quality on passenger’s satisfaction among Air Asia Passengers. A field survey of Air Asia passengers in University Utara Malaysia (UUM) in Kedah was conducted between administration staff, academic staff and students. A total of 60 questionnaires were distributed to Air Asia passengers in UUM through judgment sampling. Mean for passengers’ satisfaction state that passengers of Air Asia tend to be satisfied with the Air Asia services with the mean 4.64. Conversely, regression analysis indicated that ‘Assurance’ and ‘Reliability’ were factors that positive influence towards service quality on passenger’s satisfaction among Air Asia Passengers in UUM. These findings show that Air Asia should give attention on the factors of ‘Assurance’ and ‘Reliability’ in order to retain the passengers. Recommendation for future research was also put forward.